Coronavirus Infection an Obese Patient (Literature Review) - E. I. Panova; M. S. Pimankina (Архивъ внутренней медицины)
In the modern world the problem of obesity in combination with new coronavirus infection has acquired a special danger. On the one hand, the prevalence of obesity among the population is steadily increasing, on the other-it has been proven that obese people are among the most vulnerable in terms of increased risk of infection and a serious prognosis. This is due to the presence and peculiarities of the development of various pathological mechanisms in this category of patients. These include: high expression of angiotensin-converting enzyme 2, a high probability of a «cytokine storm» developing, maintenance of a chronic inflammatory process in adipose tissue, changes in the activity of Dipeptidyl peptidase-4 enzyme. All these processes lead to an aggravation of metabolic disorders in adipose tissue and violation of immune protection. The world medical practice in the fight against the COVID-19 pandemic shows that patients with coronavirus infection against the background of obesity more often need hospitalization in intensive care units and connection to artificial ventilation equipment. Currently, many features of the course of coronavirus infection against the background of obesity have been identified and continue to be studied. These include: the presence of severe respiratory failure, a high risk of developing respiratory distress syndrome, thrombosis and thromboembolic complications, as well as worsening of the course of chronic cardiovascular diseases. All this eventually leads to the development of severe multiple organ failure, which is often the cause of death in this category of patients.